Pie-Crusting The Medial Collateral Ligament in Arthroscopic Surgery to Overcome Difficulties in Bucket Handle Tear of Medial Meniscus Repair: A Case Report - Tarong, Yosep A; Da Costa, Alvin Danio Harta; Pratiwi, Regina Emmanuela Gusti (International Medical Journal Corp. Ltd, 2024)
Backgrounds : Around 10% of meniscus tears manifest as Bucket Handle Meniscus Tears (BHMT), where the tear extending from the red-red to red-white zones, leading to joint blockage and locking. Treatment options encompass meniscectomy or repair, with the repair meniscus shown superior outcomes for maintaining joint function and preventing arthritis. Case Report: Following a motorcycle accident, a 29-year-old man visited an orthopaedic clinic with left knee pain, swelling, and limited flexion. Physical examination revealed tenderness along the anterior medial border, restricted knee motion, and a low Lysholm Knee Score. MRI confirmed a BHMT in the posterior region. The pie- crusting method, releasing the medial collateral ligament (MCL), widens the joint gap, enhancing surgical visibility. Conclusion : This case highlights the successful application of the pie-crusting technique to address challenges linked to medial knee joint space narrowing in a posterior horn BHMT case.